INNOVATIVE APPROACHES TO CREATING A DEVELOPMENTAL ENVIRONMENT FOR PRESCHOOL CHILDREN - Kamilova Gulmira Alimovna; Bakhronova Aziza Abduraufovna (Web of Journals Publishing, 2025)
This article analyzes innovative approaches to creating a developmental environment for preschool children. In the study, the main principles of creating a comfortable environment necessary for children's education and development, as well as the importance of implementing innovative pedagogical technologies, are considered. The developmental environment for preschool children is a harmonious system of psychological, physical and social components that help to develop the child's abilities fully and effectively. The article discusses the unique aspects of STEAM-education, Montessori and Reggio Emilia methods and their use in the educational process. Innovative pedagogical approaches, including information and communication technologies, game technologies and modern methods are presented as an important factor in increasing the effectiveness of children's education. The results of the research determine the practical aspects of creating a developmental environment with the help of modern educational technologies and help pedagogues to use new pedagogical approaches.
Keywords: Innovative approaches, pedagogical technologies, STEAM technology, Montessori method, Reggio Emilia approach, information and communication technologies, game technologies, educational methods, child development, formation of educational environment, pedagogical methods, modern education.